Pendidikan Islam Multikultural (Komparasi Abdurrahman Wahid, Nurcholish Madjid dan Syafi’i Ma’arif) - Irhamuddin, Irhamuddin; Supriyoko, Supriyoko; Hasyim, A. Dardiri (Universitas Pahlawan Tuanku Tambusai, 2024)
Multicultural education is an important investment for the future. By providing inclusive education and respecting differences, we can create a generation that is more tolerant, open and ready to face global challenges. This article attempts to explain the meaning of multicultural education by Abdurrahman Wahid, Nurcholis Madjid and Ahmad Syafi'i Ma'arif by comparing and analyzing the relevance of the concept of the three ideas in education in Indonesia. Analysis This research is included in the descriptive analytic category where researchers compose descriptions and analyzes using discourse analysis to avoid overlapping data. Thus, the data analysis technique used is the descriptive analysis method. The aim of this research is firstly, Islamic education must be able to produce a young generation who is not only intellectually intelligent, but also has strong character and noble morals. Second, these three figures have provided a very valuable legacy of thought for the development of Islamic education in Indonesia. The concept of multicultural Islamic education that they promote is very relevant to the challenges of the modern era, where society lives in diversity. The three ideas presented have very high relevance in the context of education in Indonesia. The multicultural Islamic education they promote can be a solution to overcome various social problems faced by the Indonesian people, such as radicalism, intolerance and division. Examples include elementary schools studying various types of traditional food from various regions in Indonesia, making handicrafts typical of various tribes, and holding exhibitions of students' work. Middle School holds debates on social issues relevant to diversity, such as discrimination, tolerance, and human rights. Universities hold international seminars by inviting speakers from various countries to share experiences and knowledge.